2013
DOI: 10.1088/1742-6596/412/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Study of PDMS based magnetorheological elastomers

Abstract: The fabrication of conventional magnetorheological elastomers (MRE) is usually taken more than 1 day because the conventional matrixes such as natural rubber and silicone rubber need long curing time to become solid state. This study presents a rapid method for fabricating MRE within 90 minutes by using poly(dimethylsiloxane) (PDMS) as the matrix thanks to the rapid curing of PDMS in high temperature. A total of four PDMS based MRE samples were fabricated. Their mechanical and rheological properties under both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…The limit is determined at the point where the G# and G$ become dependent on the strain. Tian et al (2013) analysed the LVE region of isotropic MREs, for which they used stress-strain curves and also storage modulus-strain curves. They conclude that particle content decreases the LVE region of the MRE materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limit is determined at the point where the G# and G$ become dependent on the strain. Tian et al (2013) analysed the LVE region of isotropic MREs, for which they used stress-strain curves and also storage modulus-strain curves. They conclude that particle content decreases the LVE region of the MRE materials.…”
Section: Introductionmentioning
confidence: 99%
“…The LVE region of MRE isotropic samples is reduced with the increment of the external magnetic field (Tian et al, 2013). To determine the LVE region, Gordaninejad et al (2012) defined a linear elastic deformation at 1% of strain, because at high strains, MRE has a non-linear behaviour due to the non-linear behaviour of the compression and shear modulus.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been reported on the fundamental features of MREs [6][7][8]. These research studies share common findings whereby the baseline stiffness of the composite was kept low, and the amount of the magnetic filler particles was near the critical concentration, even for the largest changes of the material properties.…”
Section: Introductionmentioning
confidence: 81%
“…Typically, such materials are based on the use of a high-viscosity or rubber-like matrix into which particles, for example, iron, orienting along the magnetic field vector are introduced [3,4]. Performed experimental studies [5][6][7][8] show that almost all magnetically controlled materials exhibit a strong nonlinearity of their rheological properties as functions of magnetic field induction.…”
Section: Introductionmentioning
confidence: 99%